The Meaning of Work Experiences Among Coworking Space Employees: An Interpretative Phenomenological Analysis in Makassar City - Sitti Nur Khalifah Mannan; Andi Jam'an; Muhammad Najib Kasim; Muh. Asyraf Syakur (LP2M IAIN Palopo, 2026)
The rapid expansion of coworking spaces has transformed contemporary work environments by promoting flexible work arrangements, collaborative cultures, and community-oriented operations. While previous studies have predominantly examined coworking spaces from the perspective of users, limited attention has been paid to the lived experiences of employees responsible for managing daily operations. This study aims to explore how employees construct and interpret the meaning of their work experiences within coworking spaces in Makassar City, Indonesia. A qualitative research design employing Interpretative Phenomenological Analysis (IPA) was adopted to capture the subjective meanings embedded in employees' lived experiences. Data were collected through in-depth semi-structured interviews with six employees representing various operational functions, including finance, administration, customer service, facility management, operations, and community management. The findings reveal three interrelated experiential dimensions: (1) everyday operational experiences characterized by role flexibility, multitasking, and service coordination; (2) the formation of professional identity through adaptive role expansion, emotional regulation, and continuous learning; and (3) the development of work meaningfulness and job satisfaction shaped by personal growth, social relationships, organizational support, and spiritual values. The study demonstrates that employees perceive coworking spaces not merely as workplaces but as environments that continuously shape their professional identity and interpretation of work. These findings contribute to the human resource management literature by extending the understanding of employee work experiences in flexible work environments and providing practical insights for developing sustainable human resource practices in the rapidly growing coworking industry.